ChatGPT in higher education: Does acceptance lead to self-directed learning? - Najib, Khotim Hanifudin; Nofrida, Eka Ridha; Budiarto, Sulistyo; Taryatman, Taryatman; Ardhian, Trio (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2026)
ChatGPT in higher education: Does acceptance lead to self-directed learning?